Anthracycline-induced cardiotoxicity in patients with paediatric bone sarcoma and soft tissue sarcoma. (7th August 2017) - Bini, Ilaria; Asaftei, Sebastian D.; Riggi, Chiara; Tirtei, Elisa; Manicone, Rosaria; Biasin, Eleonora; Basso, Maria Eleonora; Agnoletti, Gabriella; Fagioli, Franca
Abstract: Objectives: Anthracycline cardiotoxicity is an important side-effect in long-term childhood cancer survivors. We evaluated the incidence of and factors associated with anthracycline cardiotoxicity in a population of patients diagnosed with bone or soft tissue sarcoma. Materials and methods: We retrospectively enrolled patients diagnosed with bone or soft tissue sarcoma, from 1995 to 2011, treated with anthracycline chemotherapy at our Centre and with a follow-up echocardiography carried out ⩾3 years from cardiotoxic therapy completion. Cardiac toxicity was graded using Common Terminology Criteria for Adverse Events version 4.0. Results: A total of 82 patients were eligible. The median age at treatment was 11.9 years (1.44–18). We evaluated the median cumulative anthracycline dose, age at treatment, sex, thoracic radiotherapy, hematopoietic stem cell transplantation, and high-dose cyclophosphamide treatment as possible risk factors for cardiotoxicity. The median cumulative anthracycline dose was 390.75 mg/m 2 (80–580). Of the 82 patients, 12 (14.6%) developed cardiotoxicity with grade ⩾2 ejection fraction decline: four patients were asymptomatic and did not receive any treatment; six patients were treated with pharmacological heart failure therapy; one patient with severe cardiomyopathy underwent heart transplantation and did not need any further treatment; and one patient died while waiting for heart transplantation. The median time at cardiac toxicity, from the end of anthracycline frontline chemotherapy, was 4.2 years (0.05–9.6). Cumulative anthracycline dose ⩾300 mg/m 2 (p 0.04) was the only risk factor for cardiotoxicity on statistical analyses. Conclusions: In our population, the cumulative incidence of cardiotoxicity is comparable to rates in the literature. This underlines the need for primary prevention and lifelong cardiac toxicity surveillance programmes in long-term childhood cancer survivors.